2012
DOI: 10.1258/ebm.2012.011373
|View full text |Cite
|
Sign up to set email alerts
|

The role of Fcγreceptors in atherosclerosis

Abstract: Atherosclerosis is widely considered to be an immune-mediated process. Fcγ receptors (Fcγ Rs) contribute to the regulation of a multitude of immune and inflammatory responses and are implicated in human atherosclerotic lesions. Major cell types involved in the pathogenesis of atherosclerosis express Fcγ Rs and their proatherogenic ligands such as immune complexes and C-reactive protein, which act to activate Fcγ R signaling pathways. This review summarizes recent significant progress addressing the multifacete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 88 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…On monocytes and macrophages, CRP is mostly mediated by FcγR- dependent pathways. High-affinity receptor FcγRI (CD64) and low-affinity receptor FcγRIIA (CD32) are activating receptors, while low-affinity receptor FcγRIIB (CD16) is an inhibitory receptor [ 28 , 29 ]. CRP activates FcγRs, which phosphorylate immunoreceptor tyrosine-based activating motifs, causing the activation of Syk (spleen tyrosine kinase) and in turn initiating downstream signaling cascades [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On monocytes and macrophages, CRP is mostly mediated by FcγR- dependent pathways. High-affinity receptor FcγRI (CD64) and low-affinity receptor FcγRIIA (CD32) are activating receptors, while low-affinity receptor FcγRIIB (CD16) is an inhibitory receptor [ 28 , 29 ]. CRP activates FcγRs, which phosphorylate immunoreceptor tyrosine-based activating motifs, causing the activation of Syk (spleen tyrosine kinase) and in turn initiating downstream signaling cascades [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-affinity receptor FcγRI (CD64) and low-affinity receptor FcγRIIA (CD32) are activating receptors, while low-affinity receptor FcγRIIB (CD16) is an inhibitory receptor [ 28 , 29 ]. CRP activates FcγRs, which phosphorylate immunoreceptor tyrosine-based activating motifs, causing the activation of Syk (spleen tyrosine kinase) and in turn initiating downstream signaling cascades [ 29 ]. The interaction of CRP and FcγRs promotes survival and proliferation of macrophages and enhances the release of proinflammatory molecules through stimulation of MMPs, MCP-1, and M-CSF expression and inhibition of IL-10 secretion [ 30 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for the Fc portion of immunoglobulin G (IgG), known as FcγRs, are the binding link between humoral and cellular immunologic reactions. Endothelial cells express FcγRs and pro-inflammatory mediators, such as immune complexes and C-reactive protein, that can activate FcγR-dependent pathways that lead to oxidative burst, degranulation, phagocytosis, cytokine production and antibody-dependent cell-mediated cytotoxicity (ADCC) [ 1 ]. The FcγRs are surface glycoproteins, encoded by eight genes located on chromosome 1q21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Based on structural homology and differences in affinity for IgG, this family is divided into three subfamilies: FcγRI (CD64), FcγRII (CD32) and FcγRIII (CD16). FcγR isoforms can be activating receptors (FcRI, FcγRIIA and FcγRIII) or inhibitory receptors (FcγRIIB) [ 1 ]. Two studies have demonstrated associations between certain FcγRIIA polymorphisms and coronary artery disease (CAD) and ischemic stroke [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%